Three dimensional homogenous wave equation in rectangular coordinates / Che Maisarah Amanina Che Hashim - Che Hashim, Che Maisarah Amanina (2017)
Wave equation is widely used in physics to describe small vibrations of a tightly stretched flexible string for one dimensional case. Stewart (2012) stated that the wave equations are also used to represent some physical problems in physics such as the motion of a waveform, which are an ocean wave, a sound wave, or a light wave. This project will derive the solutions of the vibrating object for obtaining the vertical displacement of a wave in three dimensional wave equation based on rectangular coordinates. In addition, the Fourier series expansion is used to find a solution. The unique solution of homogenous wave equation can be obtained by using the method separation of variables.